Pengaruh Manajemen Modal Kerja dan Rasio Aktivitas Terhadap Profitabilitas Perusahaan Manufaktur Sektor Consumer Non-Cyclicals Yang Terdaftar di BEI pada Tahun 2022-2024 - Aulia, Dita; Tanjung, Hendra; Nurmilah, Risma (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study focuses on examining the effect of working capital management and activity ratios on the profitability of consumer non-cyclical manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Working capital management is measured by the Cash Conversion Cycle (CCC), activity ratio is measured by Total Asset Turnover (TATO), and profitability ratio is measured by Return On Asset (ROA). Quantitative research method using annual financial reports as secondary data sources. The sample size used was 53 companies in the non-cyclical consumer sector, using random sampling techniques. This study uses SPSS to measure and evaluate the correlation between the research variables. The findings of this study indicate that there is no partial influence between working capital management and activity ratio on profitability ratio. Simultaneously, there is no influence between working capital management and activity ratio on profitability ratio.